BENTUK PENYAJIAN TARI SARAH HADRALMAUT PADA MASYARAKAT MELAYU DI DESA NAGUR KABUPATEN SERDANG BEDAGAI - Purnomo S (Gesture: Jurnal Seni Tari, 2015)
Sarah Hadralmaut dance comes from Hadralmaut society those are right now known as Yemenite. It is exactly in the southern peninsula of Arabic. This dance has its own characteristic in the legs movements; it is almost like Zapindance. The purpose of this research is discussing about the presentation form of Sarah Hadralmaut dance to the Malay society at the NagurBedagai village in district of SerdangBedagai. Based on the result that had been done, it can be known that Sarah Hadralmaut dance is a dance that comes from Hadralmaut area or it can be known as Yemenite - in the southern peninsula of Arabic. This dance is more dominant with the legs movement, while arms movement will adjust with the legs steps. This dance is almost the same with Zapin dance because both of them are comin from the same country that is Yemenite. Sooner or later this dance will be inherited by Malay  and become characteristic and identity of Malay . It was used to be danced by men only, but right now women are also allowed to dance.